Tests to determine the effect of reversed stresses on the elastic limit and the ultimate strength of medium steel - Lawryy, Raymond George (My University, 1903)
Introduction: Examples of repeated stresses occurring in practical work are numerous. In machinery the application of a load to a certain part rapidly and continuously, often occurs.
Citation: Lawryy, Raymond George. Tests to determine the effect of reversed stresses on the elastic limit and the ultimate strength of medium steel. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Stress Test; Steel; Tension Test; Theses